Driving Role of Institutional Investors in the Indian Stock Market in Short and Long-Run – An Empirical Study - Dasgupta, Ranjan (International Journal of Business, Economics and Management, 2014)
The process of liberalization leads to stock price appreciation followed by inflows from foreign investors in Indian stock markets. Post-1992, the FIIs become one of the prime forces to drive up or down Indian stock markets and their indices. MFs, being the most influential DIIs have alsoplayed their part. This study is endeavoured to find out the impact of and relationships between FIIs net flows, MFs net flows and the Indian stock markets as proxied by the BSE SENSEX Index, both in the long-run and short-run, by using tabular results, correlation test results, ADF and PP tests, Johansen and Juselius’s cointegration test and Granger causality test results. Monthly data are used from April, 2007 to March, 2012 for all the variables, i.e., FIIs net flows, MFs net flows and the BSE SENSEX Index. ADF and PP results show that all the variables are not integrated of the same order. Johansen and Juselius’s cointegration test is conducted based on ADF and PP results with FIIs net flows and MFs net flows with the revised long-run model. It points out at least two cointegration vectors and negative long-run relationships between FIIs net flows with MFs net flows. Then, it employs Granger causality test. The Granger causality test finds no short-run unilateral or bilateral causal relationships between the BSE SENSEX Index, and FIIs and MFs net flows and neither in between FIIs net flows with the MFs net flows. Therefore, it is concluded that, Indian stock markets have no informational efficiency. However, future studies should incorporate critical Indian and global macroeconomic variables’ impact on the FIIs net flows and MFs net flows and their short and long-run interrelationships to make the study results more conclusive and reliable.